EFEKTIFITAS PENGGUNAAN METODE CERAMAH DAN DISKUSI DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM KELAS XI DI SMAN 3 BABELAN - Rohayah, Aulia Ayu; Lathifah, Hasna; Adelin, Nur; Saleha, Tiara Nur; Khasanah, Uswatun (Piwulang: Jurnal Pendidikan Agama Islam, 2024)
The background of this study arises from the increased enthusiasm and spirit of the XI grade students at SMAN 3 Babelan in the learning process. Therefore, the purpose of this study is to explore the concept of PAI learning and its application in class XI of SMAN 3 Babelan. In addition, this study also aims to identify the factors that play a role in the increase of spirit and enthusiasm. The research method used was qualitative description, in which data collection was conducted through interviews, observations, questionnaires, and documentation. The results of interviews with teachers showed that students were more active in learning PAI through the use of lecture and discussion methods